Fruits and Vegetables Intake and Risk of Bladder Cancer: A PRISMA-Compliant Systematic Review and Dose-Response Meta-Analysis of Prospective Cohort Studies - Xu, Chang (Medicine (Baltimore), 2015)
Clinical practice recommends eating ≥2.5 cups of fruits and vegetables (FVs) each day for cancer prevention, in which the evidence from epidemiological studies for the association between FVs intake and bladder cancer (BC) prevention is inconsistent. We searched the PubMed, Embase, and Willy online Library for relevant studies published up to September 27, 2014. Prospective cohort studies investigated FVs intake, and the risk of BC with ≥3 categories of exposure was included. A dose-response meta-analysis was carried out to evaluate the association between FVs intake and risk of BC. Fourteen cohorts with 17 studies including 9447 cases were identified. No evidence of nonlinear association was examined between FVs intake and risk of BC. The summarized relevant risk (RR) of every 0.2 serving increment a day was 1.00 (95%CI: 0.99, 1.00; P = 0.17; I(2) = 41.7%; n = 14) for total fruits; 0.99 (95%CI: 0.96, 1.01; P = 0.28; I(2) = 37.0%; n = 13) for total vegetables; and 0.99 (95%CI: 0.97, 1.01; P = 0.24; I(2) = 57.5%; n = 8) for both FVs. In further analysis, we observed inverse association between every 0.2 serving increment of green leafy vegetables intake a day and risk of BC (RR = 0.98, 95%CI: 0.96, 0.99; I(2) = 0.0%; P < 0.01; Power = 0.76; n = 6), but neither for cruciferous vegetables (RR = 0.97, 95%CI: 0.93, 1.01; P = 0.19; I(2) = 55.8%; n = 8) nor for citrus (RR = 1.00, 95%CI: 1.00, 1.00; P = 0.83; I(2) = 0.0%; n = 7). Subgroup analysis showed consistent results. Little evidence supports a beneficial effect for total fruits, vegetables, both FVs, and citrus intake against bladder cancer. Green leafy vegetables may help prevent bladder cancer.